Fungus ball of the paranasal sinuses: Report of two cases and literature review - Bosi, Guilherme Rasia; de Braga, Gustavo Lisbôa; de Almeida, Tobias Skrebsky; de Carli, Adriana (International Archives of Otorhinolaryngology, 2012)
Introduction: Fungal ball of the sinuses is a not invasive infection that if characterizes for its chronicity, being the majority related with previous endodontic treatment. Affect mainly the breasts to maxillary; even so all the breasts can be involved. The main etiological agent is the Aspergillus spp. The computed tomography, had to characteristic the radiological presentations, suggests the diagnosis that is carried through definitively through histopathological analyses. The treatment standard-gold is the sinus surgery with average meatal antrostomy.Objective: Reporting two cases of fungal ball of the sinuses and to stand out important aspects of this pathology.Story of the Cases: Case 1) Patient of the feminine sex, 78 years old, presented itself with complaints of face pain has 6 months and previous history of endodontic treatment. To the physical examination it was evidenced purulent secretion presence in left average meatus. Ray X presented complete veiling of the breasts to maxillary left, while the computed tomography showed injury calcified in this place. Sinusotomy was become fulfilled that evolved well. Case 2) Patient of the feminine sex, 70 years old, looked attendance for history of sinusitis of repetition. To the physical examination no particularity was not perceived. The computed tomography, as well as the magnetic resonance, detected thickening of the mucous wall of the breasts to maxillary left, beyond a calcified mass. It was become fulfilled same sequence of treatment and the patient also evolved well.Final Considerations: The fungal infection must be considered in the patients who if present with chronic sinusitis, that they do not answer to the antibiotic use and that they possess history of endodontic manipulation.
Keywords: mycetoma; sinusitis; maxillary sinusitis; sinuses; aspergillus. droaereo and presence of hypo intense of left maxillary sinus